Risk factors and outcome of Klebsiella pneumonia sepsis among newborns in Northern India - Qazi, Mahvish; Saqib, Najmus; Raina, Rohit (International Journal of Research in Medical Sciences, 2019)
Background: The increasing clinical incidence of antibiotic-resistant bacteria is a major global health care issue. Among MDR pathogens, Klebsiella pneumoniae (KP) is one of the world's most dangerous superbugs; and becoming resistant to virtually every antibiotic available today. The objective were to study the clinical characteristics of neonatal sepsis caused by KP and the antibiotic sensitivity pattern of Klebsiella pneumoniae in a neonatal intensive care unit (NICU) in northern india. Methods: This observational study was conducted with neonates who were admitted in NICU of Government Medical College (GMC) Jammu (Jammu and Kashmir) India and whose blood culture showed growth of KP in a study period of 1 year between 1st January 2018 to 31st December 2018. The data was entered into a register and presented by descriptive statistics. Results: Twenty four neonates were included in the study. The clinical presentations include refusal of feed (83.3%), lethargy (79.2%), respiratory distress (70.8%), shock (70.8%), fever (37.5%) or hypothermia (58.3%), apnea (29.2%) and abdominal distension (33.3%). Most common perinatal risk factor was prolonged labor (>24 h) seen in 79.2% of cases. C-reactive protein (CRP) level was positive in 95% of the cases. The mortality was 25%. KP strains were sensitive to colistin, polymyxin B, cotrimoxazole and tetracyclines. Conclusions: The clinical manifestations of neonatal sepsis caused by KP are usually non-specific. CRP detection is valuable for early diagnosis of sepsis. Neonatal sepsis persists as a cause of mortality in this region. Regular antimicrobial surveillance for empirical treatment remains an important component of neonatal care.